Factors Influencing The Second-Classroom Curriculum On Academic Performance At University, China: A Literature Review - Li Xinyan; Md Nasir Bin Masran; Jin Yulu (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The second-classroom curriculum, encompassing all structured learning activities outside the formal academic program, is recognized as a crucial component of holistic education in Chinese universities. Despite its potential to enhance student competencies, many institutions report declining academic outcomes. This literature review synthesizes existing research to analyze key factors influencing the effectiveness of the second-classroom curriculum on academic performance in Chinese higher education. Through systematic analysis of recent scholarly work, four primary factors are identified: curriculum flexibility and design, learning environment resources, teachers' feedback and assessment, and student learning styles. The review further explores student engagement as a critical mediating mechanism through which these factors impact academic performance. Findings reveal that challenges including rigid curriculum structures, inadequate resources, inconsistent feedback, and mismatched learning styles hinder the potential benefits of second-classroom initiatives. A significant research gap exists in the lack of integrated models positioning student engagement as the central mediating variable within China's unique cultural context. This review concludes that future empirical research should test this proposed mediation model to provide actionable insights for optimizing second-classroom curricula to address declining academic achievement.